Comparison of Postoperative Outcomes According to Compensatory Changes of the Thoracic Spine Among Patients With a T1 Slope More Than 40°. Issue 8 (15th April 2019) - Oe, Shin; Togawa, Daisuke; Yamato, Yu; Yoshida, Go; Hasegawa, Tomohiko; Kobayashi, Sho; Yasuda, Tatsuya; Banno, Tomohiro; Arima, Hideyuki; Mihara, Yuki; Ushirozako, Hiroki; Matsuyama, Yukihiro
Abstract : Study Design: Retrospective study of postoperative outcomes of adult spinal deformity (ASD) surgery. Objective: To clarify the differences in postoperative outcomes depending on the presence or absence of thoracic compensatory changes among patients with a T1 slope (TS) more than 40°. Summary of Background Data: Loss correction after ASD surgery is more likely to occur when preoperative TS is more than 40°. When preoperative TS is more than 40°, some cases involve compensatory changes in the thoracic spine and decreased thoracic kyphosis (TK); others involve increased TK without compensatory changes. Methods: Seventy-nine patients with TS more than 40° who underwent ASD surgery were enrolled and separated into compensated and noncompensated groups (group C: TK <40°; group NC: TK ≥40°). Radiographic parameters obtained by whole-spine standing x-ray, the Oswestry Disability Index (ODI), and Scoliosis Research Society-22 (SRS-22) questionnaire were assessed. Results: There were 41 patients in group C and 38 patients in group NC. Preoperative significant differences in TS did not disappear after surgery (preoperative TS: group C and group NC = 46° and 55°, P < 0.001; just after surgery: group C and group NC = 27° and 40°, P < 0.001; 2 years later: group C and group NC = 34° and 47°, P < 0.001). There were no significant differences in ODI and all domains of the SRS-22 before surgery. However, 2 years after the surgery, ODI (38%), pain (3.5), self-image (3.0), and total (3.2) values of the SRS-22 for group NC were significantly worse than those (28%, 4.0, 3.4, and 3.5, respectively) for group C ( P < 0.05). Conclusion: Changes in the thoracic spine (TS and TK >40°) result in poor postoperative outcomes. Extending the upper instrumented vertebra (UIV) to the upper thoracic spine must be considered. Even when TS is more than 40°, TK less than 40°, and upper instrumented vertebra set to the lower thoracic level result in good postoperative outcomes. Level of Evidence: 3 Abstract : Changes in the thoracic spine (T1 slope [TS] and thoracic kyphosis [TK] >40°) result in poor postoperative outcomes. Even when TS is more than 40°, TK less than 40° and upper instrumented vertebra set to the lower thoracic level result in good postoperative outcomes.